La industrialización de la zanahoria amarilla (Daucus Carota L) y blanca (Arracacia Xanthorrhiza) como alternativa de diversificación de ingresos de los productores en la parroquia Guanujo, cantón Guaranda, provincia Bolívar, año 2021. - Tandapilco Llumitaxi, Jenny Valeria (2021)
The purpose of this work is to know the acceptance of creating the industrializing company of white and yellow carrot snacks as an alternative to diversify the income of the producers of the Guanujo parish in 2021, whose name will be “ZANAHORITAS”. In the Guaranda city, Bolívar province, the carrot snack is not produced or marketed, for this reason it is intended to enter the market by offering a new product that has nutrients, vitamins, iron and calcium and can be consumed by all people regardless of age. That being said, it is a one hundred percent natural product. It is worth mentioning that its preparation will be carried out in compliance with all quality standards that allow us to obtain economic profitability for the benefit of all the partners of the company. To begin with this work, a field investigation was carried out through direct observation, in addition, surveys that were directed to the producers of the carrot since there was a lot of production of the aforementioned product, even surveys were carried out that were applied to the consumers to later check if they would like to enjoy other types of snacks; opinion that is necessary for the rise of new ventures that are beneficial for the growth of the Province of Bolívar. It is mentioned as the main point that the profit obtained in the first year is $ 7,962.89 as observed in the Balance Point, implying that the investment of the project has an acceptable profitability Regarding the financial evaluation, a rate of 15% was calculated, obtaining the following results: Net Present Value (NPV) = $ 15,984.74 Internal Rate of Return (IRR) = 57% Investment Payback Period (PRI) = 1 year 7 months 26 days. Benefit / Cost Ratio = $ 1.19. According to the analysis, the results obtained are very favorable with respect to the financial evaluation, which means that the project can be started by the investors, since it presents a percentage of sufficient acceptance and very satisfactory profitability.